Struktur Komunitas Fitoplankton di Perairan Gambut Sungai Ambawang Desa Pancaroba Kecamatan Sungai Ambawang Kabupaten Kubu Raya - Ari Hepi Yanti, Ria Rafitri, Tri Rima Setyawati, (Jurnal Protobiont, 2015)
The Ambawang river is an area of the peat waters which is at the Pancaroba Village of Kubu Raya Regency. The purpose of this research is to know the structure of the phytoplankton communities and knowing physical-chemical water condition against the community of phytoplankton in peat water at Ambawang River, Pancaroba Village. Research carried out using purpossive sampling method. Research results retrieved 11 (eleven) genera of phytoplankton that is Achnanthes, Anabaena, Asterionella, Bambusina, Diatomae, Fragillaria, Gonatozygon, Mougeotia, Navicula, Stauroneis and Synedra. Highest abundances of phytoplankton found at Station IV with total of abundance 820.11 Ind/L. Lowest abundance of phytoplankton found at Station II with total of abundance 181.98 Ind/L. Index of Diversity (H') phytoplankton between stations ranged between 0.9409-1.4625. Index of Dominance (D) ranged between 0.2855-0,4382. Index of Equity (E) ranged between 0.3924-0.6099 and between Station I and Station II have in common a high of 100%.